Internet Banking Service Quality: Building Satisfaction and Customer Trust - Kristian Suhartadi Widi Nugraha (Universitas Pendidikan Ganesha, 2021)
This study aims to analyzes how IBSQ variables influence customer satisfaction and trust in state-owned banks in Jember Regency. The sample in this study amounted to 150 with a purposive sampling approach with data collection through questionnaires. The analysis in this study used a structural equation model (SEM-PLS). Research conducted proves that the IBSQ variables, namely personal needs, site organization, user-friendliness, efficiency, responsiveness, reliability, customer satisfaction, and customer satisfaction, affect trust. The six IBSQ variables have their variations and effects on customer satisfaction. In this study, the most significant coefficient that affects satisfaction is reliability. Reliability as the variable with the largest coefficient can be interpreted as system reliability and security, which are the top priority and guarantees in IBSQ. This study's findings indicate that it is essential for banks to improve service quality sustainably to generate competitive and consistent advantages over time. This study's overall results suggest that IBSQ as part of the banking business plays an essential role in forming customer satisfaction. Satisfaction is critical and requires consistent effort and strategy in achieving it.